Effectiveness Of Low Level Diode Laser (1064) And Acyclovir in Treatment Of Recurrent Herpes Labialis. (Comparative Clinical Study) - Gassan Y Hamed; Ahmed S Khudhur; Zaid A Alshamaa (University of Mosul, College of Dentistry, 2017)
Aims: To evaluate the clinical effectiveness of low level diode laser (1064) compared with the effect of Acyclovir (ACV) cream 5% in patients with recurrent herpes labialis (RHL). Materials and Methods: Thirty patients with active lesions (intact vesicle and rupture lesions) were included in this clinical trial. Fifteen patients were treated with low level diode laser (1064) while the other fifteen patients were treated with Acyclovir cream 5%. Results: Complete disappearance of prodromal symptoms ( itching, tingling or burning) and erythema were noticed in low level diode laser (1064) group after three days of treatment compared with ACV group. Conclusions: low level laser (1064) appeared to be more effective in healing time and pain relief than ACV cream 5%. Key words: Dental crowding; ClassII malocclusion; Dentoskeletal morphology.